Ultrasound assessment of abdominal wall muscle thickness in liver transplant recipients and healthy donors: a comparative study for the assessment of sarcopenia - Aghi Shweta; Dhingra Udit; Sindwani Gaurav; Yadav Anil; Benjamin Jaya; Bansal Kanika; Pamecha Viniyendra; Tempe Deepak K. (Journal of Ultrasonography)
Sarcopenia is a significant predictor of postoperative morbidity and mortality in liver transplant recipients. Traditional assessment tools such as computed tomography (CT) and bioelectrical impedance analysis have limitations in clinical use. This study aimed to evaluate the utility of ultrasonography (USG) in assessing abdominal muscle thickness as a marker of sarcopenia.